Correlation Between Predicted Maximal Oxygen Uptake (VO2 max) from The Six-Minute Walk Test and Reaction Time in Male Security Guards - Noor, Amira Ismi; Soehardiman, Dicky; Taufik, Feni Fitriani (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Reaction time, the interval between stimulus and motor response, reflects alertness and is critical in professions such as security guards. Maximal oxygen uptake (VO₂ max), a standard measure of cardiorespiratory fitness, has been linked to improvements in cognitive performance. This study examined the relationship between predicted VO2 max values from the six-minute walk test and reaction time in security guards. Methods: A cross-sectional study was conducted among 33 male security guards at Persahabatan National Respiratory Center between October and November 2024. Participants completed physical activity questionnaires, the six-minute walk test, and audio-visual reaction time assessments. Results: The mean predicted VO2 max was 18.3±2.9 ml/kg/min (metabolic equivalents/METs: 5.2±0.8). Body mass index significantly influenced VO₂ max (p = 0.002). Auditory reaction time was significantly faster than visual reaction time (172.6±25.7 ms vs. 199.8±33.1 ms, p < 0.001). A weak negative correlation was found between predicted VO₂ max and visual reaction time (r = –0.340, p = 0.048), but not with auditory reaction time (r = –0.245, p = 0.169). Conclusion: Higher cardiorespiratory fitness, as reflected by predicted VO₂ max, was not strongly associated with visual reaction time among security guards.